2017
DOI: 10.1111/apt.14152
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: mesalazine versus placebo in the prevention of diverticulitis recurrence

Abstract: SummaryBackgroundPrevious studies have reached conflicting conclusions regarding the efficacy of mesalazine in the prevention of recurrent diverticulitis.AimTo investigate the efficacy and safety of mesalazine granules in the prevention of recurrence of diverticulitis after acute uncomplicated diverticulitis.MethodsTwo phase 3, randomised, placebo‐controlled, double‐blind multicentre trials (SAG‐37 and SAG‐51) investigated mesalazine granules in patients with prior episodes (<6 months) of uncomplicated left‐si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
(44 reference statements)
0
40
0
1
Order By: Relevance
“…Searches of electronic databases identified 187 articles of which six RCTs , which enrolled a total of 1918 patients, were selected for this review. Overall, 1292 patients were included in the mesalazine group and 626 patients were included in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches of electronic databases identified 187 articles of which six RCTs , which enrolled a total of 1918 patients, were selected for this review. Overall, 1292 patients were included in the mesalazine group and 626 patients were included in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies enrolling 1367 patients compared a mesalazine dose of > 2 g/day with placebo. The risk of recurrence of diverticulitis was higher in the mesalazine group (OR 1.28, 95% CI 1.02–1.62, P = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…We thank Drs Gracie and Ford for their editorial on our study . We fully agree that the use of mesalazine for preventing recurrence of true diverticulitis cannot be recommended.…”
mentioning
confidence: 72%
“…The role of anti-inflammatory, aminosalicyclate (5 ASA) compounds to counteract this, including mesalazine has been investigated. However, multiple placebo controlled trials have shown that they neither reduce recurrent episodes nor improve symptomatology [23,24]. These findings are confirmed in a 2017 systematic review and meta-analysis of 8 randomised controlled trials.…”
Section: Mesalazine and Probioticsmentioning
confidence: 92%